Trusted solution monitoring system based on ZigBee wireless sensor network - Tian-shu WANG; Gong-xuan ZHANG; Xi-chen YANG (Tongxin xuebao, 2017)
In the greenhouse environment,the concentration of nutrient solution was always ignored.At the same time,the core node coordinator of the ZigBee wireless monitoring system was easily compromised.A trusted solution monitoring system based on ZigBee wireless sensor network was designed and implemented.Firstly the hardware structure of sensor,router and coordinator was introduced.Then the processes of external voltage measurement and data cleaning were illustrated.For realizing the trusted boot of the coordinator,trusted u-boot to measure the integrity of some key files was designed.Experimental results show that the solution concentration data could be sent from each node to the monitoring computer and the remote terminal.At the same time,the trusted module of the coordinator can detect the captured coordinator node and warning.Therefore,the designed system has strong function and security.